Development and application of a ray-tracing code integrating with 3D equilibrium mapping in LHD ECH experiments. (12th November 2015) - Ii Tsujimura, T.; Kubo, S.; Takahashi, H.; Makino, R.; Seki, R.; Yoshimura, Y.; Igami, H.; Shimozuma, T.; Ida, K.; Suzuki, C.; Emoto, M.; Yokoyama, M.; et al.
Abstract: The central electron temperature has successfully reached up to 7.5 keV in large helical device (LHD) plasmas with a central high-ion temperature of 5 keV and a central electron density of m −3 . This result was obtained by heating with a newly-installed 154 GHz gyrotron and also the optimisation of injection geometry in electron cyclotron heating (ECH). The optimisation was carried out by using the ray-tracing code ' LHDGauss ', which was upgraded to include the rapid post-processing three-dimensional (3D) equilibrium mapping obtained from experiments. For ray-tracing calculations, LHDGauss can automatically read the relevant data registered in the LHD database after a discharge, such as ECH injection settings (e.g. Gaussian beam parameters, target positions, polarisation and ECH power) and Thomson scattering diagnostic data along with the 3D equilibrium mapping data. The equilibrium map of the electron density and temperature profiles are then extrapolated into the region outside the last closed flux surface. Mode purity, or the ratio between the ordinary mode and the extraordinary mode, is obtained by calculating the 1D full-wave equation along the direction of the rays from the antenna to the absorption target point. Using the virtual magnetic flux surfaces, the effects of the modelled density profiles and the magnetic shear at the peripheral region with a given polarisation are taken into account. Power deposition profiles calculated for each Thomson scattering measurement timing are registered in the LHD database. The adjustment of the injection settings for the desired deposition profile from the feedback provided on a shot-by-shot basis resulted in an effective experimental procedure.